The effect of different traditional Chinese exercises on bone mineral density in menopausal women: a systematic review and network meta-analysis - Hou, Jun; Mao, Haiping; Xie, Peiyao; Cui, Yuemei; Rong, Ming (Frontiers in Public Health, 2024)
Objective: To evaluate the optimal choice of traditional Chinese exercise (TCE) for improving bone mineral density in postmenopausal women through a network meta-analysis. Methods: The Chinese and English databases were searched, including China National Knowledge Infrastructure, Chongqing VIP, PubMed, Web of Science and Cochrane Library. The outcomes included BMD of lumbar L2-L4, femoral neck, ward triangle, and greater trochanter. Standardized mean differences (SMD) and 95% confidence intervals (CI) were used to assess the correlation between each group of interventions, and surface under the cumulative ranking (SUCRA) was used to rank the best interventions. Results: A total of 20 randomized controlled trials (RCTs) including 1933 subjects and six interventions:(Tai Chi (TC), Baduanjin (BDJ), Wuqinxi (WQX), Yijinjing (YJJ), TA (Tai chi plus calcium supplementation), BA (Baduanjin plus calcium supplementation)) and three control measures:(Calcium supplementation (CA), Aerobic exercise (AE), Not exercise intervention (NEI)) were analyzed. Regarding BMD of lumbar L2-L4: TC [SMD= 0.99 (0.62,1.37)], BDJ [SMD= 2.12 (1.39,2.85)], TA [SMD= (1.12(0.17,2.07)], BA [SMD= 2.24 (1.16,3.31)] were superior in increasing BMD of lumbar L2-L4 relative to NEI. Regarding BMD of femoral neck: TC [SMD= 1.24 (0.70,1.78)], BA [SMD= 3.77 (1.98,5.56)] were superior in increasing BMD of femoral neck relative to NEI. Regarding BMD of ward's triangle: TC [SMD= 1.63 (1.09,2.17)] was superior in increasing BMD of ward's triangle relative to NEI. Regarding BMD of greater trochanter: TC [SMD= 0.98 (0.28,1.68)] were superior in increasing BMD of greater trochanter relative to NEI. TC topped the SUCRA with BMD of lumbar L2-L4: 53.8, femoral neck: 74.9, ward's triangle:86.9 and greater trochanter: 77.7. Conclusion: four TCE (TC, BDJ, TA and BA) are all effective in partially improving BMD indicators in postmenopausal women, while TC was effective on all four BMD indicators, which seems to be recommended as the most suitable exercise modality for postmenopausal women.